PENINGKATAN PRODUKTIVITAS KELOMPOK SANTRI DALAM BUDIDAYA JAMUR TIRAM PUTIH DI PONDOK PESANTREN DARUL HUDA, JABON, SIDOARJO - Nima’tuzahroh Nima’tuzahroh; Fatimah Fatimah; Nur Indradewi Oktavitri (Universitas Airlangga, 2018)
Islamic boarding schools generally have human and natural resources, and have a large influence on the communities around them. These resources can be optimized to increase students’ productivity with White Oyster Mushroom (JTP) cultivation. This community service aims to implement JTP cultivation to increase students’ productivity. The method that was carried out was to increase the knowledge of JTP cultivation, the formation of JTP cultivation cadres for making kumbung, JTP cultivation, JTP harvesting and sales. The JTP results show that the students’ insight increased by an average of 73% through the pretest and posttest scores during socialization. 3 Cadres are formed from coordination with the head of the cottage. The location chosen for mushroom cultivation is based on the criteria for JTP cultivation. JTP cultivation cadres have been able to make 4 x 6 m mushroom kumbung around the hut. Cultivation is done using 2000 baglog mushrooms for 1 month. Increased net income from santri through harvesting mushrooms from Rp. 0 to Rp. 4,000,000 every 2000 baglog after harvest. This increase in income can show an increase in santri productivity for income for Islamic boarding schools.AbstrakPondok pesantren umumnya memiliki sumber daya manusia dan sumber daya alam, dan memiliki pengaruh besar terhadap masyarakat di sekitar mereka. Sumber daya tersebut dapat dioptimalkan untuk peningkatan produktivitas santri dengan budidaya Jamur Tiram Putih (JTP). Pengabdian masyarakat ini bertujuan untuk penerapan budidaya JTP untuk peningkatan produktivitas santri. Metode yang dilakukan adalah peningkatan wawasan budidaya JTP, pembentukan kader budidaya JTP untuk pembuatan kumbung, berbudidaya JTP,pemanenan dan penjualan JTP. Hasil JTP menunjukkan wawasan santri meningkat rata-rata sebesar 73% melalui nilai pretest dan post test saat sosialisasi. 3 Kader dibentuk dari koordinasi dengan ketua pondok. Lokasi yang dipilih untuk budidaya jamur berdasarkan kriteria untuk budidaya JTP. Kader budidaya JTP telah mampu membuat kumbung jamur dengan ukuran 4 × 6 m di sekitar pondok. Budidaya dilakukan dengan menggunakan 2000 bag log jamur selama 1 bulan. Peningkatan penghasilan bersih dari santri melalui panen jamur dari semula Rp. 0 menjadi Rp. 4.000.000 tiap 2000 baglog setelah panen. Peningkatan penghasilan ini dapat menunjukkan peningkatan produktivitas santri untuk pemasukan bagi pondok pesantren.